2017
DOI: 10.1088/1361-6420/aa8cb2
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and efficient practical procedures for the generation of inflation factors for ES-MDA

Abstract: The ensemble smoother with multiple data assimilation (ES-MDA) has proved to be a powerful assisted history-matching method. The main drawback of ES-MDA is that the inflation factors for damping the changes in model parameters have to be determined before starting the historymatch. Although various authors have provided suggestions for determining the inflation factors adaptively as the history-match proceeds, these methods often result in a large number of data assimilation steps which can make ES-MDA too com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
103
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(106 citation statements)
references
References 47 publications
2
103
0
1
Order By: Relevance
“…For nonlinear problems, the choice of the α k 's and N a has a major impact in the performance of the method. There are recent works proposing methods to select α k 's and N a [27,9,39,30,10]. However, here we use simplest choice, which consists of selecting N a in advance and setting α k = N a , for k = 1, .…”
Section: Data-space Inversion With Ensemble Smoothermentioning
confidence: 99%
“…For nonlinear problems, the choice of the α k 's and N a has a major impact in the performance of the method. There are recent works proposing methods to select α k 's and N a [27,9,39,30,10]. However, here we use simplest choice, which consists of selecting N a in advance and setting α k = N a , for k = 1, .…”
Section: Data-space Inversion With Ensemble Smoothermentioning
confidence: 99%
“…The next sections present two procedures to compute α 1 . The first procedure was originally presented by Rafiee and Reynolds (2017) and the second is proposed in this paper.…”
Section: Geometric Selection Of Es-mda Inflationmentioning
confidence: 99%
“…Moreover, these schemes usually require several data assimilation steps, often more than ten. Recently, Rafiee and Reynolds (2017) proposed to select the inflation factors in a geometrically decreasing order where the first inflation is based on the regularization condition of (Hanke, 1997). For a simple test problem, they showed that the geometric scheme resulted in smoother permeability fields compared to constant inflations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations